Post-Graduation Career Preferences of Medical Students of Karachi and the Determinants Behind Expected Brain Drain - Naseem Dhedhi; Faisal Ahmed; Bushra Rabbani; Kanwal Naz; Muhammad Zulfiqar Hyder Naqvi; Nadia Farooq (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: The objective of the study was to determine the reasons affecting career choice for post-graduation and decision of studying abroad among undergraduate students in a medical university of Karachi. Methods: A cross-sectional study was conducted among students of 1stto 5th year MBBS program of  Baqai Medical University, Karachi from March 2022 to August 2022. A questionnaire was filled by students who voluntarily wished to participate. Statistical Package for Social Sciences version 21 was used for data analysis.   Results: The most common clinical fields of choice for post-graduation of medical students were cardiothoracic surgery (14.3%), followed by general surgery (13.6%), whereas the most common non-clinical fields of choice were medical education (53.3%) followed by research (20.0%). A majority of students (54.5%) wished to pursue post-graduation abroad. Among those opting for staying in Pakistan, almost half of them wished to work in rural areas (n=69, 50.4%) and the remaining in urban areas (49.6%). Conclusion: The most popular clinical fields of choice for post-graduation among medical students turned out to be cardiothoracic surgery whereas the non-clinical career switch was mostly towards medical education. Moreover, a majority of students wished to pursue their post-graduation abroad. Key words: Career Choice, Specialty, Medical, Emigration, Students, Medical